2011
DOI: 10.1016/j.ygeno.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and transcriptomic analyses distinguish classic Rett and Rett-like syndrome and reveals shared altered pathways

Abstract: Rett syndrome (RTT) is an X-linked neurodevelopmental disorder characterized by derangements in nervous system especially in cognition and behavior. The present study aims to understand the molecular underpinnings of two subtypes of RTT, classic RTT and Rett-like, and to elucidate common pathways giving rise to common RTT phenotype using genomic and transcriptomic approaches. Mutation screening on selected nuclear genes revealed only MECP2 mutations in a subset of classic RTT patients. MLPA assays and mtDNA sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 68 publications
1
25
0
Order By: Relevance
“…Mental retardation disorders like Rett syndrome (Tropea et al, 2009;Colak et al, 2011), incontinentia pigmenti (Gautheron et al, 2010), and mutations in the TRAPPC9 gene (Philippe et al, 2009) are associated with an altered, but distinct IKK/NF-B signaling signature. To understand how the newly identified IKK/ NF-B-Igf2-Igf2R axis is mechanistically involved in these diverse cases of mental retardation opens a promising future field of research especially as the need for cutting-edge therapeutic approaches will constantly rise within the field of neuropsychiatric diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Mental retardation disorders like Rett syndrome (Tropea et al, 2009;Colak et al, 2011), incontinentia pigmenti (Gautheron et al, 2010), and mutations in the TRAPPC9 gene (Philippe et al, 2009) are associated with an altered, but distinct IKK/NF-B signaling signature. To understand how the newly identified IKK/ NF-B-Igf2-Igf2R axis is mechanistically involved in these diverse cases of mental retardation opens a promising future field of research especially as the need for cutting-edge therapeutic approaches will constantly rise within the field of neuropsychiatric diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Primers sequences for both genes and others are available as an online document (Table S1, Supporting Information). The entire coding region of the mitochondrial genome was amplified and sequenced as described elsewhere . PCR for nuclear genes was performed according to standard protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Being a symptom complex rather than a specific diagnosis, patients with ASD have been found to have single gene mutations as well as cytogenetic aberrations identified by conventional analysis and fluorescence in situ hybridization (FISH). The more recent technology of cytogenomic microarray analysis (CMA) has identified an increasing number of copy number gains and losses present in patients with ASD [Cook and Scherer, 2008; Glessner et al, 2009; Colak et al, 2011] In 2009, Glessner et al identified seven patients with ASD who had a chromosome 6 copy number loss involving the PARK2 gene region. Control patients did not show this copy number loss.…”
Section: Introductionmentioning
confidence: 99%